FACTORS AFFECTING CASH DIVIDEND: EMPIRICAL STUDIES ON THE PROPERTY COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE PERIOD 2010-2013 - Marziyanda, Suci; Rodoni, Ahmad (Universitas Esa Unggul, 2016)
Abstract Industry competitiveness for the companies that have already listed increased. Therefore, dividend payment is an important decision. In general, dividend payment consists of cash dividend and stock dividend. Many factors that impact dividend payment and that matters become concern in this research, especially cash dividend. This paperâs objectives is for analyzing factors that impact on dividend payment on the property companies that listed in the Indonesia Stock Exchange (IDX) period 2010-2013. Independence variables that utilized on this paper are cash ratio, earning per share, and return on investment. Sampling methodology that utilized is purposive sampling with samples total eleven companies. Analysis method is quantitative method, regression analysis panel data. Research result explain that cash ration, earning per share, and return on investment significantly impact cash dividend.Â Key words : Cash Ratio, Earning per Share, Return on Investment, Cash Dividend